(3GdcTchd aj eMGSf Gdbhds - (3GdSfhSj , eMeO Hf Ydj Hf GdSfhSj, CHh YHO Gddg,J (B1276 (3g` s
(3ChdgG (B:s
(3Gddge Ud Ydi ef efg GfTbJ GdCSQGQ, hGfadbJ GdCfhGQ, hYdi Bdg GdCNjGQ jbhd cGJHg hCSjQ PfHg eMeO GHJOCJ aj LeY s
(3BNQgG (B:s
(3LGA GdReGf HdjdI YTQGA ef MSfgG NdjJ ef GdQbHGA s
(3dYdgG eShOI GdeDda HNWgs
(3hHChdgG hBNQgG QSGFd JbQjXs
(3gfGc Tc aj YfhGf GdcJGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B299 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B14s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B151 s
Keywords: (3GdCOHs